The Analysis of Factors that Affecting the Amount of Free- Range Chicken Meat’s Consumption in Langkat Regency - Siti Aisyah; Iskandar Sembiring; Hasnudi .; Yunilas .; Edhy Mirwandhono (Universitas Sumatera Utara, 2018)
Chicken meat is one of the livestock commodities that can meet the protein needs of the community, but there are constraints on the price side. The price of free-range chicken meat tends to fluctuate due to production and demand imbalances and has an impact on price increases. Therefore, there needs to be control so that price increases that occur in free-range chicken meat do not jump sharply The purpose of the study was to determine the factors that influence the amount of freerange chicken meat’s consumption in Langkat Regency. The study was conducted in June - August 2018. The method that used in sampling was the proportionate stratified random sampling method and used the Slovin formula. Primary data collection was carried out by interview techniques using questionnaires to respondents and secondary data collection was obtained from the agencies and agencies assembled and then analyzed with Multiple Linear Regression using SPSS 22 application. The results showed the amount of free-range chicken meat’s consumption in Langkat Regency was influenced partially by income and the number of family members with R² = 0.61.